Synthesis, Spectroscopic, Thermodynamic and Biological Activity Studies of Schiff base and Metal Complexes derived from 2-[(1H-Pyrrol-2-ylimino methyl)]- 5-(2-hydoxy-phenyl)-[1,3,4-thiadiazol] - Shalan, Nasser; Balkhi, Abdelmijd; Hamo, Samh; Falah, Ahmad (Al-Nahrain Journal of Science, 2014)
New metal complexes of type M2(HL)2.4H2O[(M = Co(II), Ni (II) and Cu (II)] were prepared using the ligand (HL) =2-[(1H-Pyrrol-2-ylimino methyl)]- 5-(2-hydoxy-phenyl)-[1,3,4-thiadiazol]. The Schiff bases were was condensed from [1H-Pyrrole-2-carbaldehyde] with [2-amino-5-(2-hydroxy-phenyl-1,3,4-thiadiazole] in alcoholic medium. The prepared complexes were characterized by FTIR, UV-vis, 1H-NMR and mass spectra as well as magnetic susceptibility measurements, thermal analysis. The activation thermodynamic parameters, such as ΔE*, ΔH*, ΔS* and ΔG* are calculated from the TGA curve using Coats-Red fern method. From the spectral measurements, structures for the complexes were proposed. Preliminary in vitro tests for antimicrobial activity show that all prepared compounds display good activity to Staphylococcus aureus, Escherishia coli, Pseudononas aeroginosa and Cndida albicans.